Respuesta :

Wolfyy

Answer:

h = -13

Step-by-step explanation:

Use PEMDAS to solve this problem.

11h - 5(h + 3) = -63

~Use distributive property to simplify [ a(b + c) = ab + ac ]

11h - 5h + 15 = -63

~Combine like terms

6h + 15 = -63

~Subtract 15 to both sides

6h = -78

~Divide 6 to both sides

h = -13

Best of Luck!

Answer:

Step-by-step explanation:

11h - 5(h + 3) = -63

-Multiply parenthesis so

-5(h) + -5(3) = -5h - 15

New equation: 11h - 5h - 15= -63

                                   +15  +15

(add 15 to both sides)

[tex]6h=-48\\\\\frac{6h}{6} =\frac{-48}{6} \\ \\ h=-8[/tex]

h = -8